The effect and mechanism of exercise for post-stroke pain - Ma, Yue; Luo, Jing; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
One of the common negative effects of a stroke that seriously lowers patients’ quality of life is post-stroke pain (PSP). Thus, exercise in PSP management has become a hot research topic. The main advantages of exercise therapy are affordability and ease of acceptance by patients compared to other treatment methods. Therefore, this article reviews the effectiveness and possible mechanisms of exercise interventions for PSP. Exercise training for patients with PSP not only improves physical function but also effectively reduces pain intensity and attenuates the behavioral response to pain. In addition, exercise therapy can improve brain function and modulate levels of pro-inflammatory and neurotrophic factors to exert specific analgesic effects. Potential mechanisms for exercise intervention include modulation of synaptic plasticity in the anterior cingulate gyrus, modulation of endogenous opioids in vivo, reversal of brain-derived neurotrophic factor overexpression, inhibition of purinergic receptor (P2X4R, P2X7R) expression, and inhibition of microglia activation. However, current research on exercise for PSP remains limited, and the sustainable benefits of exercise interventions for PSP need to be further investigated.